GROWTH OF GOSTFISH, Upeneus sulphureus IN KENDARI BAY, SOUTHEAST SULAWESI - Asriyana Asriyana; Nur Irawati (Jurusan Perikanan dan Kelautan, 2017)
Research on growth and condition factor of goatﬁsh were carried out from May 2015 to November 2015 in Kendari Bay, Southeast Sulawesi. The purpose of this researchwas to analyze growth and condition factor of goatﬁsh in Kendari Bay, Southeast Sulawesi. Fish samples were collected using bottom experimental gillnets and trammel nets with different mesh sizes ¾, 1, 1¼, and 1½ inch.Growth parameters were analyzed following von Bertalanffy formula using ELEFAN I software of package program of FiSAT II. A total of 386 individual ﬁsh was caught with ranged from 46–176 mm in the total length and 3,1 – 67,1g in weight. The length-weight relationship of goatﬁsh is Lt= 184,42 1E–1;5(t006)